Comorbidity, multimorbidity, dual diagnosis — synonyms or different terms? - O. M. Drapkina; A. M. Shutov; E. V. Efremova (Кардиоваскулярная терапия и профилактика)
The authors express their opinion on the problem of the terminology of the combined pathology in modern clinical practice. The terms “comorbidity”, “multimorbidity”, “dual diagnosis” are considered in terms of conceptual differences. The issues of diagnostics, classification and modern clinical recommendations for patients with combined pathology are also discussed. Given the variety of terminology and the ambiguity of the semantic component in the discussion of the problem of comorbidity/ multimorbidity, it seems justified for the medical community to come a common consensus in terms of terminology, classification and diagnosis. It will help to avoid mistakes and disagreements between physicians of various specialties.